Análise do perfil empreendedor: um estudo em microempresas de Pau dos Ferros-RN - Limeira, Emilyanno Saraiva (Universidade Federal Rural do Semi-Árido, 2021)
Entrepreneurship has become part of Brazilians' daily lives since the 1990s, with economic opening and increased competitiveness. The main objective of this work was to identify the microentrepreneur profile of the city of Pau dos Ferros-RN, located 392 km from Natal, capital of Rio Grande do Norte. The present study was divided in three stages, the first one being associated to a bibliographical research, in order to serve as theoretical framework of the research, the second part was characterized by the use of the qualitative method applied through a field research, in which it was applied A questionnaire about characteristics of an entrepreneur, and soon afterwards the analysis of these data was done so that the entrepreneur profile of the microentrepreneur could be identified. Finally, the analysis of the data was carried out, in order to verify the profile of the microentrepreneurs of Pau dos Ferros. Thus, it was observed that the economic activity of selling clothing, footwear and jewelry as the majority in a percentage of 21.8%. It was verified that 63.3% are males and 36, 2% are females. The age group in which they are located is between 41 and 50 years old, with 29.8% and with regard to the reasons that led to starting the enterprise 53.7% stated that it was by family influence. As for the educational level, 75.5% have high school. Finally, most companies have less than 10 years of existence with 45.2%. This paper offers the opportunity to promote future studies, since it is a fundamental theme to understand the process of economic development in the region and the real influence of entrepreneurship, as a primordial element, for economic and social evolution.
Keywords: Perfil; Profile; Microempresa; Microenterprise; Empreendedor; Entrepreneur; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA